2020
DOI: 10.1088/1361-6641/ab6104
|View full text |Cite
|
Sign up to set email alerts
|

Si microline array based highly responsive broadband photodetector fabricated on silicon-on-insulator wafers

Abstract: We report a high responsivity broad band photodetector working in the wavelength range of 400-1100 nm made from a horizontal array of Si microlines (line width ∼1 μm) fabricated on a silicon-on-insulator (SOI) wafer. The array was made using a combination of plasma etching, wet etching and electron beam lithography. It forms a partially suspended (nearly free) Silicon microstructure on SOI. The array detector under full illumination of the device shows a peak Responsivity of 28 A W −1 at 750 nm, at a bias of 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…9 In recent years, it has been shown that high can also be obtained in an array of nano/microlines of suspended Si made on standard silicon-oninsulator (SOI) wafers with an MSM configuration. 10,11 The suspension leads to inhibition of carrier recombination at the Si/SiO 2 interface in SOI wafers. Table 1 response may indeed share a common physics with almost all semiconductor NWs, although the quantitative extent may vary depending on the material specificity.…”
Section: Pmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In recent years, it has been shown that high can also be obtained in an array of nano/microlines of suspended Si made on standard silicon-oninsulator (SOI) wafers with an MSM configuration. 10,11 The suspension leads to inhibition of carrier recombination at the Si/SiO 2 interface in SOI wafers. Table 1 response may indeed share a common physics with almost all semiconductor NWs, although the quantitative extent may vary depending on the material specificity.…”
Section: Pmentioning
confidence: 99%
“…Large values of have been observed in a wide class of materials that include elemental semiconductors like Si and Ge, compound semiconductors like GaAs, GaN, and InAs, oxide semiconductors like ZnO (the ZnO NWs have diameters between 150 and 300 nm), and even in molecular semiconductor Cu:TCNQ . In recent years, it has been shown that high can also be obtained in an array of nano/microlines of suspended Si made on standard silicon-on-insulator (SOI) wafers with an MSM configuration. , The suspension leads to inhibition of carrier recombination at the Si/SiO 2 interface in SOI wafers. Table shows a compilation of published results on parameters of photodetectors made from single semiconductor NWs.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Broad band high responsivity in single Si NW and Si NWs array based detectors have been achieved using similar concepts. 12,13 These single NW detectors can function as self-biased (zero applied bias) detectors with high responsivity of the order of 10 4 A/W with Si NW 12 and 10 5 A/W with Ge NW. 14 Inspite of ultrahigh responsivity over a broad spectral range and extremely low power dissipation, these detectors suffer from the disadvantage that the fabrication process is lithography intensive and needs availability of nano-lithography facilities.…”
Section: Introductionmentioning
confidence: 99%
“…An example of utilizing the surface oxide and band bending as an active agent of inhibiting carrier recombination has been done for a single Ge NW-based broadband (300–1100 nm) photodetector, where a peak responsivity of 10 7 A/W at low power consumption has been achieved. , Broadband high responsivity in single Si NW- and Si NW array-based detectors has been achieved using similar concepts. , These single NW detectors can function as self-biased (zero applied bias) detectors with high responsivity of the order of 10 4 A/W with Si NW and 10 5 A/W with Ge NW . Despite ultrahigh responsivity over a broad spectral range and extremely low power dissipation, these detectors suffer from the disadvantage that the fabrication process is lithography-intensive and needs the availability of nanolithography facilities.…”
Section: Introductionmentioning
confidence: 99%
“…These substrates are used for opto-electronic applications as well [2,3]. Recently high sensitivity broad band opticaldetectors (UV to NIR) have been produced by fabricating micro and sub-micron width arrays on SOI wafers [4,5].…”
Section: Introductionmentioning
confidence: 99%